An investigation of market reactions on legal insider trading : a research on the Portuguese Stock Market - Corrêa, Francisco do Carmo Ribeiro (2013)
This dissertation investigates the market reaction, parameterized by Cumulative Abnormal Returns (CARs), to transactions performed by insiders of companies listed on PSI-Geral, assuming these trades have important information content, and outsiders believe on the superior information insiders’ possess. An event-study methodology to measure the impact of these trades on a 50-working day window is used. Purchases (sales) are followed by positive (negative) statistically significant abnormal returns, and the strongest market reaction is felt on the days following the communication of trades to CMVM. To control for other specific insider and firm characteristics, a cross-sectional regression framework was run and was found strong relation between volume of transaction, holdings of insiders, firm size, book to market ratios and CARs. Results also show improvements on the enforcement of insider trading legislations, in comparison with past legal frameworks.